Cost Recovery Rate Tarif Rumah Sakit dan Tarif INA-CBG’s Berdasarkan Clinical Pathway pada Penyakit Arteri Koroner di RSUP Dr. Mohammad Hoesin Palembang Tahun 2015 - Mardiah, Mardiah (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2016)
This study aims to see how the difference between the cost recovery rate (CRR) hospital rates and INA CBG's rates in case of CAD with PCI at Hospital Dr. Mohammad Hoesin Palembang. The results showed the cost of treatment based on clinical pathways are at the severity level I value of CRR Hospital rates above the CRR CBGs INA rates, whereas the severity level II of CRR Hospital rate more lower than CRR INA CBGs rates for the utility stent is less than 2. At severity level III CRR INA CBGs with utilization rates of stent 1 and 2 higher than the CRR INA CBGs rate. This is due to CBGs INA rate do not take into account the magnitude of the stent in every act of PCI performed in patients with CAD. Based on the research necessary to evaluate the methode of calculating INA CBGs rates from hospital base rate methode to Cost of treatment based on clinical pathway in order to create a balance so that the operational cost of service rates hospitals can be met and still be able to provide good quality services.